England is the Largest Center for Online Gambling Activity in the World, Versus Indonesia is Exposed to Online Gambling Emergency Stage Five - Junaedi Junaedi (International Journal of Law, Crime and Justice, 2024)
Gambling is not only prohibited by Islamic law but gambling is also prohibited by law. Online gambling in Indonesia has a widespread, deep and pervasive impact, like an octopus. The dangers of gambling grip various aspects of individual and societal life, creating complex and layered problems. From financial and mental health losses to family breakdown and increased crime.Online gambling is the act of gambling carried out online via a website or application that provides gambling content. Please note that online gambling is an act that is prohibited based on the provisions in Article 27 paragraph (2) of the ITE Law, namely that every person intentionally and without right distributes and/or transmits and/or makes accessible electronic information and/or electronic documents containing content. Gambling.The largest online gambling market in the world with gross online gambling revenue globally is estimated to reach US$102 billion or the equivalent of IDR 1,563.35 trillion in 2021 (exchange rate IDR 15,327/US$).The UK is recorded as the largest online gambling market in the world with revenues of US$12.48 billion, the United States (US) with revenues of US$10.96 billion, and Australia US$6.55 billion. Meanwhile, the largest online gambling players in Indonesia are in the West Java region, estimated at 535,644 people, with transactions of IDR 3.8 trillion, DKI Jakarta, with 238,568 players with transactions of IDR 2.3 trillion, Central Java has 201,963 players with transactions of IDR 1.3 trillion. Trillion, Banten 150,302 players with transactions of IDR 1.02 trillion, and East Java 135,227 players with transactions of IDR 1.05 trillion.The dangers of Gambling in terms of increased crime, many individuals are trapped in huge debts due to gambling which triggers and spurs them to turn to criminal acts such as theft, fraud, and even violence to earn money, creating an unsafe social environment.